Hubungan Tingkat Pendidikan Terhadap Kejadian Tuberkulosis Paru - Emir Yusuf Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Tuberculosis is a disease caused by Mycobacterium Tuberculosis. This bacterium attacks the lungs but does not rule out attacking other body parts. This disease can be transmitted through coughs containing Mycobacterium Tuberculosis and spread into the air. Indonesia is one of the countries in the world that has a high prevalence of tuberculosis and is still increasing in the number of cases each year. Education level is one of the factors that influence the incidence of tuberculosis. The higher the level of one's education, the lower the incidence of tuberculosis. This is because someone who has a high level of education can obtain and absorb information better about tuberculosis, so it is easy to take precautions to avoid getting tuberculosis. In addition, the higher level of education of a person will indirectly affect the level of health.